2013
DOI: 10.1186/1471-2121-14-25
|View full text |Cite
|
Sign up to set email alerts
|

Syndecan-2 is upregulated in colorectal cancer cells through interactions with extracellular matrix produced by stromal fibroblasts

Abstract: BackgroundThe extracellular matrix (ECM) influences the structure, viability and functions of cells and tissues. Recent evidence indicates that tumor cells and stromal cells interact through direct cell-cell contact, the production of ECM components and the secretion of growth factors. Syndecans are a family of transmembrane heparan sulfate proteoglycans that are involved in cell adhesion, motility, proliferation and differentiation. Syndecan-2 has been found to be highly expressed in colorectal cancer cell li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 41 publications
(51 reference statements)
0
31
0
2
Order By: Relevance
“…Syndecan-1 was observed in all (8 of 8) normal tissue samples and all cancer tissues, with the exception of one (sample 8) that showed enhanced levels of syndecan-1. Interestingly, the expression pattern of syndecan-2, which is normally highly expressed in colon carcinoma (Beauvais and Rapraeger, 2004;Han et al, 2004;Vicente et al, 2013), did not show enhanced levels in the cancer tissues studied. Our data seem to correlate better to a report indicating that colon cancer cell lines HT29 and Caco-2 that show reduced syndecan-2 expression, and the report that decreased levels of syndecan-2 do not influence proliferation and invasion by these cell lines (Han et al, 2004).…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…Syndecan-1 was observed in all (8 of 8) normal tissue samples and all cancer tissues, with the exception of one (sample 8) that showed enhanced levels of syndecan-1. Interestingly, the expression pattern of syndecan-2, which is normally highly expressed in colon carcinoma (Beauvais and Rapraeger, 2004;Han et al, 2004;Vicente et al, 2013), did not show enhanced levels in the cancer tissues studied. Our data seem to correlate better to a report indicating that colon cancer cell lines HT29 and Caco-2 that show reduced syndecan-2 expression, and the report that decreased levels of syndecan-2 do not influence proliferation and invasion by these cell lines (Han et al, 2004).…”
Section: Resultsmentioning
confidence: 83%
“…significantly reduced in highly metastatic colon carcinoma cells (Vicente et al, 2013). Oh and co-workers (Han et al, 2004) showed that Caco-2 and HT29 cells endogenously expressed as low levels of syndecan-2, whereas HCT116 cells expressed high levels of syndecan-2, in the same type of human colon adenocarcinomas.…”
Section: Figmentioning
confidence: 97%
“…The role of HSPGs on cell adhesion, which is dependent on the interaction of HS chains with ECM proteins such as fibronectin, has already been well established (38). Apparently the decrease of the sulfation status of HS facilitated the adhesion and migration of colorectal cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…4A) was observed. Interestingly, this increased adhesion was more significant when cells overexpressing SULFs were plated on fibronectin, which is known to bind HS and participate in the adhesion of colorectal cancer cells (38).…”
Section: Sulfs Increase Cancer Cells Adhesion and Invasivenessmentioning
confidence: 99%
See 1 more Smart Citation